Evaluation the Role of Malondialdehyde in Occurrence and Development of Diabetic Retinopathy Patients (Medico Legal Update, 2021)
Case control study was carried out in Salah-Addin city in private ophthalmology clinic from 1st November of2019 to End february 2020. The study included 90 individuals including sixty diabetic patients (30 who hadretinopathy and 30 without retinopathy) and 30 healthy individuals to evaluate the level of Malondialdehyde(MDA) in diabetic patients with and without retinopathy and healthy controls. All patients were agedbetween (51-82) years, with a negative history of antioxidant supplementation consumption. Blood sampleswere collected from each patients and controls to evaluate the levels of malondialdehyde and HbA1c byusing immunofluorescence technique. The study showed that majority of diabetic retinopathy (DR) patientswere females and the highest mean of age was recorded in diabetic retinopathy patients (60.76±7.25year) compared with diabetic without retinopathy patients (58.31±9.19 year). The study displayed thatthe highest mean of MDA was recorded in DR patients as compared with diabetic without retinopathypatients (390.37±108.68 vs 336.97±94.95 ng/ml), although the result was non-significant (P: > 0.05).The study showed that the highest mean of MDA was in DR patients (390.37±108.68 ng/ml) followed bydiabetic without retinopathy patients (336.97±94.95 ng/ml) and the lowest mean was in healthy individuals(293.32±42.51 ng/ml), (P: < 0.05). The study showed that, HbA1c was elevated significantly (P